THE TOXICITY OF MAULI BANANA (MUSA ACUMINATA) STEM WATER EXTRACT ON BONE MARROW MESENCHYMAL STEM CELL IN VITRO - CARABELLY, AMY NINDIA; ASPRIYANTO, DIDIT; APRIASARI, MAHARANI LAILLYZA; RIZKY, SELVIANA (International Journal of Applied Pharmaceutics, 2019)
Objective: Since mesenchymal stem cells (MSC) can differentiate into bone, cementum, and periodontal ligament, they can be used to treat aggressive periodontitis. The limited number of MSCs requires replenishment of growth factor in the cell culture process. Since growth factor is quite expensive, an alternative material is needed. Mauli banana stem has antioxidant and immunomodulatory properties. Methanol extract of Mauli banana stem is known to be toxic toward MSCs; therefore, another solvent with a non-toxic effect is needed, such as a water solvent. We analyzed the toxicity of Mauli banana stem water extract on MSC in vitro. Methods: In this laboratory experimental (true experimental) study with a Post-test Only Control Group Design, MSC cultures were treated with Mauli banana stem water extract at 10, 20, 40, 60, 80, and 100 mg/mL dosages. One group without any treatment served as a control group and one was a media control group. Each group was incubated for 24 h and then was given 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide reagent and analyzed by an enzyme-linked immunosorbent assay (ELISA) reader. Results: One-way analysis of variance showed a significant difference. Conclusion: Mauli banana stem water extracts at 10, 20, 40, and 60 mg/mL were not toxic toward MSC in vitro, while dosages of 80 and 100 mg/mL dosage were toxic.